(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: John Cunningham virus (JCV) is among important Polyomaviridae family, which is involved in PML and nephropathy among renal transplant recipients (RTR), and they become reactivate in immunodeficient situations. Objective: To find out the seroprevalence rate of JC polyomavirus among (RTR) and healthy persons. Methods: A case-control study to detect the presence of JCV IgG antibody in serum samples collected from a total of 400 samples were taken from (200) healthy blood donors as control individuals and (200) RTR age and sex-matched, at the period between February 2021 to March 2022. New experimental indirect enzyme linked immunosorbent assay kit had been designed and manufactured manually for detection Anti-JCV IgG in both RTR group and control group. Results: The results revealed 36 out of 200 (18%) cases of RTR have IgG, while in the control group only 24 out of 200 (12%) were positive for this antibody, no statistically significant difference was noticed between the study groups. However, there was significantly higher mean serum IgG titer in RTR patients as compared to control group (p= 0.016). Conclusion: Seroprevalence of JCV is relatively lower among Iraqi subjects as compared to other countries both RTR and healthy controls, but the IgG titer is increasing during immunosuppression suggesting possible reactivation of the virus among RTR. Keywords: Seroproprevalance, JCV, Kidney transplant recipients, IgG Citation: Hussein RK, Al-Obaidi AB, Hussein MR. Prevalence of Anti JC Polyomavirus IgG in A sample of Iraqi kidney transplant recipients and healthy blood donors. Iraqi JMS. 2023; 21(2): 193-199. doi: 10.22578/IJMS.21.2.7